Price vs Quantity in a Repeated Differentiated Duopoly - Luca Lambertini; Christian Schultz (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
We investigate the choice of market variable, price or quantity, of an optimal implicit cartel. If the discount factor is high, the cartel can realize the monopoly profit in both cases. Otherwise, it is optimal for the cartel to rely on quantities in the collusive phase if goods are substitutes and prices if goods are complements. The reason is that this minimizes the gains from deviations from collusive play.
Keywords: 330